1999
DOI: 10.1159/000018137
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid-Induced Pancreatitis in Patients with Autoimmune Bullous Disease: Case Report and Prospective Study

Abstract: Corticosteroid pulse therapy using very high doses may produce corticosteroid-induced pancreatitis (CIP) that is unexpected during conventional oral corticosteroid therapy and may sometimes be fatal. Our goal was to evaluate the relation between pulse corticosteroid administration and pancreatitis. A case of CIP is reported, and a prospective study was performed. Corticosteroid pulse therapy followed by 30 mg prednisolone orally was utilized in 7 hospitalized patients with autoimmune bullous disease, and serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Although the pathophysiological mechanism behind corticosteroid-induced pancreatitis remains unclear, recent data suggest it may be related to the systemic effects of these medications, and specific alterations of lipid and calcium metabolism in pancreatic cells 4. The current literature on epidemiological incidence of oral corticosteroid use suggests that the risk of acute pancreatitis was increased among current users compared with non-users, and the risk for development of this condition was highest 4–14 days after the medication was taken 3.…”
Section: Discussionmentioning
confidence: 99%
“…Although the pathophysiological mechanism behind corticosteroid-induced pancreatitis remains unclear, recent data suggest it may be related to the systemic effects of these medications, and specific alterations of lipid and calcium metabolism in pancreatic cells 4. The current literature on epidemiological incidence of oral corticosteroid use suggests that the risk of acute pancreatitis was increased among current users compared with non-users, and the risk for development of this condition was highest 4–14 days after the medication was taken 3.…”
Section: Discussionmentioning
confidence: 99%
“…Several case studies have reported development of acute pancreatitis linked with oral glucocorticoid use. [11][12][13][14][15][16] In 2 case reports, acute pancreatitis recurred following readministration of dexamethasone 14 and prednisone. 16 However, more epidemiological studies are warranted before the association can be established.…”
Section: Commentmentioning
confidence: 99%
“…10 In addition, several case reports have described induction of acute pancreatitis in patients treated with glucocorticoids. [11][12][13][14][15][16] In 2 of these case reports, there was a positive rechallenge with oral dexamethasone 14 and prednisone. 16 Importantly, some indications of glucocorticoid therapy, eg, inflammatory bowel disease, 17 systemic lupus erythromatosus, 18 and Wegener granulomatosis, 19 could be risk factors for acute pancreatitis resulting in confounding by indication.…”
mentioning
confidence: 99%
“…Therefore it is difficult to conclude that the pancreatitis results from GC toxicity and not from other drugs or combinations of drugs. A study by Yoshizawa et al (69) demonstrated that patients with autoimmune blistering diseases showed an elevation in serum pancreatic enzymes within several days after the pulse dosing in a dose‐dependent manner. Therefore careful monitoring of pancreatic function in this patient population is recommended (69).…”
Section: Management Of Patients Receiving Gcs and Prevention Of Side mentioning
confidence: 99%